2011
DOI: 10.5539/ijef.v3n6p233
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Macroeconomic Variables on Stock Market Index in China and India

Abstract: This paper investigates the relationships between stock market indices and four macroeconomics variables, namely crude oil price (COP), money supply (M2), industrial production (IP) and inflation rate (IR) in China and India. The period covers in this study is between January 1999 to January 2009. Using the Augmented Dickey-Fuller unit root test, the underlying series are tested as non-stationary at the level but stationary in first difference. The use of Johansen-Juselius (1990) Multivariate Cointegration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 39 publications
(24 reference statements)
12
62
0
6
Order By: Relevance
“…The results found that macroeconomic variables significantly influence stock market indices. However, the VEC equilibrium time-series model applied by others (Adeleke and Gbadebo, 2012;Agrawalla and Tuteja, 2008;Chaudhuri and Smiles, 2004;Filis, 2010;Herve et al, 2011;Hess, 2004;Hosseini et al, 2011;Karacaer and Kapusuzoglu, 2010;Kyereboah and Agyire, 2008;Maysami and Koh, 2000;Muradoglu et al, 2001;Nasseh and Strauss, 2000;Patra and Poshakwale, 2006;Wong et al, 2006) to explore the long-run and short-run equilibrium relationships between macroeconomic variables and stock market indices. These studies revealed that macroeconomic variables significantly change stock market indices.…”
Section: Review Of Previous Empirical Studiesmentioning
confidence: 99%
“…The results found that macroeconomic variables significantly influence stock market indices. However, the VEC equilibrium time-series model applied by others (Adeleke and Gbadebo, 2012;Agrawalla and Tuteja, 2008;Chaudhuri and Smiles, 2004;Filis, 2010;Herve et al, 2011;Hess, 2004;Hosseini et al, 2011;Karacaer and Kapusuzoglu, 2010;Kyereboah and Agyire, 2008;Maysami and Koh, 2000;Muradoglu et al, 2001;Nasseh and Strauss, 2000;Patra and Poshakwale, 2006;Wong et al, 2006) to explore the long-run and short-run equilibrium relationships between macroeconomic variables and stock market indices. These studies revealed that macroeconomic variables significantly change stock market indices.…”
Section: Review Of Previous Empirical Studiesmentioning
confidence: 99%
“…In addition the variables in goods market are not appropriate indicators to forecast the future stock index movement. Hosseini et al (2011) study the role of four macroeconomic variables which are the crude oil price, money supply, industrial production and inflation rate on stock market index in China and India employing Johanse-Juselius multivariate cointegration and Vector eroor correction model technique. The study found a short run and long run linkage between macroeconomics variable and stock market index in both countries.…”
Section: Introductionmentioning
confidence: 99%
“…Stock returns are found to be significantly influenced by exchange rates, inflation rates and the S&P 500 Index while returns are not influenced by interest rate, gross domestic product, money supply and oil prices. Hosseini et al (2011) studied the relationships between stock market indices and four macroeconomics variables including crude oil price, money supply, industrial production and inflation rate in China and India for the period January 1999 to January 2009. Results suggest both long and short run linkages between macroeconomic variables and the stock market index in both countries.…”
Section: Literature Reviewmentioning
confidence: 99%